Sistem Pengelolaan Persediaan Berdasarkan Pola Hubungan Antar Produk Buah Olahan Menggunakan Association Rule Mining - Siska Vadilah; Yulison Herry Chrisnanto; Puspita Nurul Sabrina (Prosiding SISFOTEK, 2020)
association rule is analogous to a shopping basket. From the shopping basket the supermarket visitors will be able to know, what items are often bought together and which items are not. CV. Anugrah Paris Van Java is a company engaged in the processing of processed fruits such as ready-to-drink juice, concentrate and syrup. Customer's buying patterns are influenced by product inventory. The process of managing product inventory is managed manually so that there is a buildup of less desirable products. A frequent case is the lack of processed fruit products due to a lack of calculation from the purchase of raw materials. Based on these problems, a system for determining the pattern of relationships between processed fruit products was built as new knowledge to help the factory in the supply of processed fruit products. The method used in the system to be built is using the Association Rule Mining method with a priori algorithm. Based on research results, this system can display inventory recommendations based on analysis using association rule mining.